Der Kampf gegen das Presse-Imperium : die Anti-Springer-Kampagne der 68er-Bewegung - Jung, Dae Sung (Histoire, 2016)
The Anti-Springer Campaign (ASK) of the 1968 movement was not only a struggle against the opinion monopoly of the Springer publishing house - it was also a central factor in the mobilization of the extra-parliamentary opposition (APO), whose players were the market power and the reporting of the conservative publishing houses. Dae Sung Jung's historical study shows how the ASK became a central project of many student and non-student groups and thus became the common denominator of the APO